Dimensionality Analysis of Magnetotelluric Data Crossing the Sumatran Fault System at Aceh Segment - Khumaidi Khumaidi; Fadhli Fadhli; Nazli Ismail (Universitas Syiah Kuala, 2013)
Dimensionality of magnetotelluric transfer functions have been analyzed crossing the Sumatran Fault System at Aceh segment. The research was aimed to determine strike direction of the fault system using magnetotelluric transfer function data. We used Phoenix Geophysics MTU-5A equipment in range frequency 5A equipment in range frequency 0.86-320 Hz for data measurement. Collection of data was performed along two profiles with spacing between stations vary from 7 to 80 Km. The first profile started 94.5 Km from Aceh Jaya District and ended at Pidie District. The second profile started 16.5 Km from Aceh Jaya District and ended at Bireuen District.The data were analyzed by using Zhang et al. (1989) method to calculate Swift's skew and strike direction. Based on the calculation, we found that the Swift's skew values were generally less than 0.1, which were usually the overall structure of local and regional and they could be viewed as a 1D or 2D, and the values above 0.1 were considered as 3D effects or noises. Furthermore, the average strike has 0º or 90º angle. The data showed that geoelectrical strikes of both profiles were in agreement with the geological structure of the fault system. In order to get image of the 2D resistivity model of the area, we had inverted the magnetotelluric data showed that geoelctrical strikes of both profiles were in agreement with the geological structure of the fault system. In order to get image of the 2D resistivity model of the area, we had inverted the magnetotelluric data using MT2DinvMatlab (Lee et al., 2009). The model showed clearly position and depth of the fault lines along the profiles.